Peran Gereja Dalam Mengajarkan Perdamaian Di Tengah Masyarakat Majemuk - Emiyati, Ayang; Mardin, John; Ricard, Ricard (Didache: Journal of Christian Education, 2023)
Pluralism cannot be separated from Indonesian society, pluralism is a color in society. In society the issue of peace is an issue that cannot be separated from the role of a religious institution, including the church. Peace is the responsibility of the whole society, even a pluralistic society, including the church. The role of the church is very vital in impacting peace. The church is in the midst of a pluralistic society, so the church is directly involved in teaching peace in a pluralistic society. Of the several cases of conflict that have occurred in Indonesia, the church has played an important role in peace, namely teaching tolerance and teaching the importance of living in peace. The formulation of the problem in this research is what are the roles of the church in teaching peace missions in a pluralistic society? The purpose of this research is to describe the role of the church in teaching peace missions in a pluralistic society. the method used is library research with a descriptive approach. The role of the church in teaching peace in a pluralistic society is: teaching tolerance, teaching the importance of living in peace and living in love.